2021
DOI: 10.1186/s40942-021-00319-3
|View full text |Cite
|
Sign up to set email alerts
|

Vogt-Koyanagi-Harada Syndrome following COVID-19 and ChAdOx1 nCoV-19 (AZD1222) vaccine

Abstract: The challenge of COVID-19 has rapidly changed medical management worldwide. The relatively small time from pandemic to vaccines regulatory approval triggered a race toward vaccines development. However, important questions regarding SARS-CoV-2 vaccines remain. A case of complete Vogt-Koyanagi-Harada (VKH) Syndrome that occurred 4 days following SARS-CoV-2 vaccination and another patient that developed VKH 14 days post COVID-19 clinical onset are presented. A causal relationship between COVID-19 and uveitis may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 22 publications
0
51
0
Order By: Relevance
“…Ocular inflammatory events after COVID-19 vaccination from a multinational case series are described in this study. A search of Medline, using PubMed and Google Scholar, performed in August 2021, using the following keywords: ‘uveitis’, ‘vaccination’, ‘COVID-19’, revealed six case reports and two national case series describing presumed COVID-19 vaccine-related uveitis have been reported so far, including new onset of bilateral juvenile idiopathic arthritis (JIA)-associated anterior uveitis, unilateral anterior uveitis, bilateral choroiditis complicated by subretinal fluid, bilateral panuveitis with choroidal thickening and vascular leakage, and recurrence of Vogt Koyanagi Harada (VKH) [ 19 26 ]. Rabinovitch et al reported twenty one cases of uveitis after COVID-19 vaccination in Israel, of which nineteen were diagnosed with anterior uveitis and two developed multiple evanescent white dot syndrome (MEWDS) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular inflammatory events after COVID-19 vaccination from a multinational case series are described in this study. A search of Medline, using PubMed and Google Scholar, performed in August 2021, using the following keywords: ‘uveitis’, ‘vaccination’, ‘COVID-19’, revealed six case reports and two national case series describing presumed COVID-19 vaccine-related uveitis have been reported so far, including new onset of bilateral juvenile idiopathic arthritis (JIA)-associated anterior uveitis, unilateral anterior uveitis, bilateral choroiditis complicated by subretinal fluid, bilateral panuveitis with choroidal thickening and vascular leakage, and recurrence of Vogt Koyanagi Harada (VKH) [ 19 26 ]. Rabinovitch et al reported twenty one cases of uveitis after COVID-19 vaccination in Israel, of which nineteen were diagnosed with anterior uveitis and two developed multiple evanescent white dot syndrome (MEWDS) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a three week follow up, the patient remarkably demonstrated visual acuity of 20/20 in both eyes with no signs of inflammatory activity and resolution of the exudative retinal detachments. Of note, the authors also described a case of VKH which developed in a 37-year-old female patient two weeks after she tested positive for COVID-19 on a polymerase chain reaction (PCR) test-i.e., in the setting of COVID-19 infection-as opposed to after vaccination [51]. Similarly, the patient had vision loss and signs of inflammation: She had KPs OD, mild vitritis bilaterally, and fluorescein angiography demonstrated bilateral optic disc hyperfluorescence due to leakage.…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 97%
“…In another report, Saraceno et al described a 62-year-old female who developed acute bilateral loss of vision two days after receiving the AZD1222 vaccine [51]. She was found to have visual acuity of 20/600 OD and 20/200 OS.…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 99%
“…The retina and the uvea are the most commonly involved ocular structures following COVID-19 vaccination with 50 cases reported in the literature, 21 being contributed by a retrospective study from Israel [ Table 3 ]. [ 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ] The mean age was 43.6 ± 17.2 (median 40) years with 23 males and 23 females (unspecified in 4). The symptoms developed at a median interval of 4 (mean 7.4 ± 8.5 ) days from the time of vaccination.…”
Section: Posterior Segment Manifestations Of Covid-19 Vaccinementioning
confidence: 99%
“…Viral infections have been known to trigger VKH with cytomegalovirus (CMV), influenza A, hepatitis C being implicated. [ 18 ] Antigenic cross-reactivity, HLA-DR4 status of patient (with influenza A), and interferon have been the mechanisms suggested in relation to viral infections causing VKH. Bacillus Calmette-Guerin (BCG) vaccine, influenza, hepatitis B, and yellow fever vaccinations have all been reported to cause cases of VKH, the onset ranging from 3 days to 4 weeks.…”
Section: Posterior Segment Manifestations Of Covid-19 Vaccinementioning
confidence: 99%